PROFIL KOMPETENSI LITERASI SAINS SISWA SMP KELAS IX SE-KECAMATAN KOTABUMI - Lia Septya; Tri Jalmo; Berti Yolida (Universitas Lampung, 2016)
This study aimed to know the profile science literacy competence of students IX grade from Kotabumi North Lampung Academic Year 2015/2016. Design of this study was simple descriptive used purposive sampling with 329 samples. Qualitative data that were external and internal factors that affecting science literacy competence which analyzed from questionnaires percentage of students and teachers, while quantitative data were the science literacy competence of students which analyzed from the scores of PISA test questions. The results showed students' science literacy competencies were in the category